Synthesis of temperature-responsive Dextran-MA/PNIPAAm particles for controlled drug delivery using superhydrophobic surfaces - Lima, A. C. (2011)
Purpose: To implement a bioinspired methodology using superhydrophobic surfaces suitable for producing smart hydro- gel beads in which the bioactive substance is introduced in the particles during their formation. Methods: Several superhydrophobic surfaces, including polystyrene, aluminum and copper, were prepared. Polymeric solutions composed by photo-crosslinked dextran-methacrylated and thermal responsive poly(N-isopropylacrylamide) mixed with a protein (insulin or albumin) were dropped on the superhydrophobic surfaces, and the obtained millimetric spheres were hardened in a dry environment under UV light. Results: Spherical and non-sticky hydrogels particles were formed in few minutes on the superhydrophobic surfaces. The proteins included in the liquid formulation were homogeneously distributed in the particle network. The particles exhibited temperature-sensitive swelling, porosity and protein release rate, with the responsiveness tunable by the dextran-MA/PNIPAAm weight ratio.Conclusions: The proposed method permitted the preparation of smart hydrogel particles in one step with almost 100% encapsulation yield. The temperature-sensitive release profiles suggest that the obtained spherical-shaped biomaterials are suitable as protein carriers. These stimuli-responsive beads could have potential to be used in pharmaceutical or other biomedical applications, including tissue engineering and regenerative medicine.